Peran dan Manfaat Arbitrase sebagai Alternatif Penyelesaian Sengketa Ditinjau dari Perspektif Pelaku Usaha - Indradewi, Astrid Athina; Sugianto, Fajar (Jurnal Hukum dan Sosial Politik, 2024)
Every person experiences disagreements, conflicts, issues, and confrontations in their lifetime. Nobody wants to get into a disagreement with someone else. Each business actor, particularly in economic activities, should always be prepared for the possibility of disagreements that may arise at any point in the future. Here, the business actor will select the form of dispute resolution that best fits their requirements. This study employed a normative juridical research methodology that combines a doctrinal and statutory regulation approach. This study concludes that arbitration is a non-litigation dispute settlement mechanism. With its many benefits, arbitration plays a big part in settling business conflicts.